ARABIKA COFFEE MARKETING STRATEGY SARA ATE MULTI-BUSINESS COOPERATION (KSU) IN ACEH TENGAH REGENCY - Baihaqi, Akhmad; Jannah , Raudhatul; Romano; Atikah, Qhisthina (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Sara Ate Multipurpose Cooperative (KSU), established in 2013 in Aceh Tengah Regency, has the main objective of prospering its members through family principles. The cooperative is engaged in trading Gayo Arabica coffee, both in the domestic and international markets. With the number of members increasing to 1,200 and the plantation area reaching 1,300 hectares by 2024, KSU Sara Ate continues to focus on exporting premium quality green beans. In addition to providing economic benefits, the cooperative also plays a role in social aspects such as education, environment, and society. This research was conducted at Sara Ate Multipurpose Cooperative (KSU) in Aceh Tengah Regency, which is known as an Arabica coffee-producing area. The selection of this location was based on the unique characteristics of the region. The research was conducted in Aceh Tengah Regency using purposive sampling method, involving key individuals within KSU Sara Ate to analyze external factors and develop effective marketing strategies. The purposive sampling method was used to select specific respondents who have important roles in the cooperative. The ETOP method was used to analyze external factors affecting the cooperative, while SWOT analysis was used to determine an effective marketing strategy by considering the opportunities, threats, strengths, and weaknesses faced by the company. The results of the study, through SAP and ETOP analysis, found that KSU Sara Ate is in a dominant and speculative position, which indicates high strengths and opportunities for success but with equivalent risks. Therefore, the most appropriate strategy is to make short-term investments to ensure future success.